Beyond the Classroom: From Education for Rural Transformation to Learning Within Rural Transformation? - Pant, Anna-Robinson (Journal of Education and Research, 2016)
Much research and policy has focused on improving the performance and reach of formal educational institutions in rural areas. Debates within education and development have been largely concerned with analysing the relationship between different levels of schooling and various indicators of well-being. Such research has usually been framed within an economistic discourse: associating education and learning primarily with schools and formal providers, and assuming that only formally educated people can facilitate development and rural transformation. This limited starting point has led to privileging investigation into formal learning and to a neglect of alternative lenses for researching people’s everyday learning in rural areas. Drawing on the methodology and findings of an IFAD-UNESCO project, this article proposes an alternative approach to researching and theorising learning in rural areas. In place of focusing on formal education and an entry point through educational providers, centre stage – the study team conducted ethnographic-style research on how young people learned skills and knowledge informally and exploring the relationship between informal, non-formal and formal learning. The findings challenged many assumptions around a linear ‘literacy first’ and teacher-centred model of development, revealing that so-called ‘illiterate’ people had often developed their own innovative strategies for learning new skills, such as mobile phones. The paper concludes by reflecting on the implications of this research study for educational researchers, policy makers and practitioners seeking to develop greater understanding of the complex relationship between education and rural livelihoods.